Heat Treatment Effects on Microstructural and Thermal Properties of High Cu Content NiTiCu Shape Memory Alloy - Tatar, Cengiz; Haji, Azad Ibrahim; Qader, Ibrahim Nazem (Springer Int Publ Ag, 2021)
Characterization of shape memory alloys (SMAs) is important to determine and improve specific properties for a variety of applications. In this study, an arc-melting device was used to create a high Cu content NiTiCu SMA, which was then aged at 1073, 1123, 1173, and 1223 K. Vickers microhardness, differential scanning calorimetry, optical microscope, and scanning electron microscopy-energy dispersion X-ray spectroscopy (SEM-EDS) instruments were used to investigate the mechanical, thermal, and microstructural properties of the aged alloys. The alloys showed a single step (B2 <-> B19) phase transformation for the measured range of temperatures. The activation energy decreases as the aging temperature increases up to 1173 K. The crystallite size for the alloys aged at 1073 was around 320 nm, while it increased to about 450 and 550 nm for the alloys aged at 1173 and 1223 K, respectively. It was found that the heat-treated alloys have a larger crystallite sizes compared to equiatomic NiTi SMAs and an as-casted NiTiCu SMA produced in the same condition. Also, the hardness of B19 (matrix) was less than that of the Ti-2(Ni, Cu) precipitated phase.
Keywords: Heat treatment; Shape memory alloy; Characteristics; Microstructure; Activation energy